Conductivity, structure, and thermodynamics of Y2Ti2O7–Y3NbO7 solid solutions. Issue 31 (24th July 2020) - Winiarz, Piotr; Mielewczyk-Gryń, Aleksandra; Lilova, Kristina; Wachowski, Sebastian; Subramani, Tamilarasan; Abramchuk, Mykola; Dzik, Ewa; Navrotsky, Alexandra; Gazda, Maria
Abstract : Defect fluorite yttrium niobate Y3 NbO7 and pyrochlore yttrium titanate Y2 Ti2 O7 solid solutions are single-phase oxygen ion- and proton-conducting materials. Abstract : The defect fluorite yttrium niobate Y3 NbO7 and pyrochlore yttrium titanate Y2 Ti2 O7 solid solutions have been synthesized via a solid state synthesis route. The resulting stoichiometry of the oxides is Y2+ x Ti2−2 x Nb x O7, where x = 0 to x = 1. All of the samples were single-phase; however, for those with a predominant fluorite phase, a small amount of additional pyrochlore phase was detected. The volume of the solid solution unit cells linearly increases with increase in yttrium niobate content. The water uptake increases with ( x ) and the protonic defect concentration reaches almost 4.5 × 10 −3 mol mol −1 at 300 °C. The calculated enthalpy of formation from oxides suggests strong stability for all of the compositions, with the values of enthalpy ranging from −84.6 to −114.3 kJ mol −1 . The total conductivity does not have a visible dependence on Y3 NbO7 content. For each compound, the total conductivity is higher in wet air. Interestingly, for samples where x < 0.5, the ratio of conductivity in hydrogen to air increases with increasing temperature, while for x > 0.5, the trend is the opposite.